Aggressive granular cell ameloblastoma: Report of a rare case - N Aravindha Babu; S Leena Sankari; N Anitha; Gouse Mohideen (Wolters Kluwer Medknow Publications, 2015)
Granular cell ameloblastoma is a slow growing odontogenic ectodermal tumor. The tumor shows typical ameloblastoma with the cells showing eosinophilic granularity. This variant of ameloblastoma is aggressive with high recurrence rates. We report a case of aggressive ameloblastoma of granular cell variant